Dissecting the functional significance of endothelin A receptors in peripheral nociceptorsin vivovia conditional gene deletion - Stösser, Sebastian; Agarwal, Nitin; Tappe-Theodor, Anke; Yanagisawa, Masashi; Kuner, Rohini (Pain, 2010)
The peptide endothelin-1 (ET1), which was originally identified as a vasoconstrictor, has emerged as a critical regulator of a number of painful conditions, including inflammatory pain and tumor-associated pain. There is considerable pharmacological evidence supporting a role for endothelin A receptors (ETA) in mediating ET1-induced pro-algesic functions. ETA receptors are expressed in small-diameter nociceptive neurons, but also found in a variety of other cell types in peripheral tissues, including immune cells, keratinocytes, endothelial cells, which have the potential to modulate nociception. To elucidate the functional contribution of ETA receptors expressed in sensory neurons towards the functions of the ET1 axis in pathological pain states, we undertook a conditional gene deletion approach to selectively deplete expression of ETA in sensory nerves, preserving expression in non-neural peripheral tissues; the expression of ETB remained unchanged. Behavioural and pharmacological experiments showed that only late nociceptive hypersensitivity caused by ET1 is abrogated upon a loss of ETA receptors on nociceptors and further suggest that ET1-induced early nociceptive hypersensitivity involves activation of ETA as well as ETB receptors in non-neural peripheral cells. Furthermore, in the context of alleviation of cancer pain and chronic inflammatory pain by ETA receptor antagonists, we observed in corresponding mouse models that the contribution of ETA receptors expressed in nociceptors is most significant. These results help understand the role of ETA receptors in complex biological processes and peripheral cell-cell interactions involved in inflammatory and tumor-associated pain.